The Impact of Macroprudential Supervision on the Capital Operation of Commercial Banks - Zhu, Chen; Chen, Liping (Journal of Accounting, Business and Finance Research, 2018)
Based on the 8320 observations in 40 quarters of 16 listed banks, this paper empirically analyses the macro-prudential supervision’s impact on commercial bank’s capital operation through the dynamic unbalanced panel system GMM model. The results show that macro-prudential supervision has exerted active supervision on China’s commercial banks, guiding China’s commercial banks to establish a capital restraint mechanism and improving the bank’s internal capital supplement mechanism. The response of commercial banks to capital supervision is positive. The regulatory rating results influence the active adjustment of the bank’s follow-on capital ratio. Commercial banks basically meet the requirements for prudent management of countercyclical capital. Based on the analysis of the data in the article, this paper suggests that the regulatory authorities further strengthen the bank’s capital supervision and make the bank’s macro-prudential supervision appear more counter-cyclical. At the same time, we must appropriately improve the banking ownership structure, increase the sources of external funds for commercial banks, and enhance the transparency of the financial system so that uninsured loan holders can play a significant role in binding banks.